The Legal Position of Wives and Children Resulted from Siri Marriage in the Distribution of Inheritance Based on Equity - Damasynta, Anisya Devi Aprilia (Jurnal Konstatering, 2022)
This study aims to determine and analyze the legal position of the siri wife and the children of the siri marriage in the division of inheritance based on justice. To find out how the position of the siri wife, the position of the children resulting from the siri marriage and the legal consequences of the position of the siri wife and children in the distribution of inheritance based on justice. The approach method in this study is a normative juridical approach. The research specifications are analytical descriptive. The type of data required includes primary data, which includes the Civil Code, UUP No. 1 of 1974, KHI, PP No. 9 of 1975 concerning Implementation of UUP No. 1 of 1974, MK Decision No. 46/PUU-VIII/2010, Al-Qur'an and secondary data, namely books, magazines, websites, research results and/or scientific papers from legal circles that are related to the topic to be discussed. Collecting research data by reviewing and reviewing document studies or library materials. The data analysis method used in analyzing the data is a qualitative analysis method. The results of the study show that the position of a siri wife according to religious law is valid if it fulfills the pillars and conditions for a valid marriage even though it is not registered. According to the provisions in Article 2 paragraph (1) of the Marriage Law, a marriage is valid if it is carried out according to the laws of each religion and belief. This means that if a marriage meets the requirements and the pillars of marriage or Ijb Kabul have been carried out (for Muslims), then the marriage is valid, especially in the eyes of religion and public beliefs. But the validity of this marriage in the eyes of religion and public belief needs to be legalized again by the State, in which case the provisions are contained in Article 2 paragraph (2) of the Marriage Law. However, there are still many people who do not care about the registration of marriages, which results in the status of children being born. Second, related to the position of the siri children born from the siri marriage only having civil relations with the mother and the mother's family, the illegitimate child from the siri marriage does not obtain his rights to the maximum in a country based on law. And third, related to the legal consequences of the siri wife and siri children in the distribution of inheritance that the siri wife is not entitled to a living and assets gono like this in the event of a divorce and the siri children only have an inheritance relationship with their mother and her mother's family.Keywords: Distribution; Inheritance; Marriage; Wife.